2019
DOI: 10.4317/jced.55378
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge in pre-school children: A survey among parents in central Italy

Abstract: Background The aim of this survey was to evaluate the knowledge and awareness of parents about potential oral health risk factors and correct management of oral hygiene of their preschool children. Material and Methods The participation to the survey was proposed to all parents of 3-5 year aged children attending a kindergarten in Campobasso. A self-administered questionnaire was completed to obtain information regarding demographic and education variables, knowledge ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
0
20
0
4
Order By: Relevance
“…Oral health knowledge of schoolchildren is influenced by socioeconomic factors, such as gender, ethnicity, type of school, income as well as the educational level of their parents [9,22,23]. A recent study by Calcagnile et al indicated that not all parents in Italy are well informed with the oral hygiene of their children and, consequently, an oral health promotion is highly recommended [24]. Greater attention to visit the dentist regularly and maintain oral health is demonstrated by parents with a high educational level and sufficient income [22,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Oral health knowledge of schoolchildren is influenced by socioeconomic factors, such as gender, ethnicity, type of school, income as well as the educational level of their parents [9,22,23]. A recent study by Calcagnile et al indicated that not all parents in Italy are well informed with the oral hygiene of their children and, consequently, an oral health promotion is highly recommended [24]. Greater attention to visit the dentist regularly and maintain oral health is demonstrated by parents with a high educational level and sufficient income [22,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…8,9,12 It was reported that the development of caries can be decreased with parental supervision in addition to tooth brushing. 36,37 Our participants were university students, and thus parental guidance probably plays less of a role than it does for younger students. In addition, the participants' monthly income did not seem to significantly contribute to oral hygiene knowledge or behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This result was unexpected and differs from the findings of previous studies, which have shown significant correlations between socioeconomic status and oral hygiene. 35,36 This finding might be explained by a lack of oral health knowledge, which negatively affects participants' behaviors. Furthermore, participants who frequently brushed and flossed had better oral health knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…16 During the preschool period, parents are the primary persons responsible for their children's oral health, so parents should acquire su cient oral-health knowledge and implement relevant oral-healthpromotion activities to control their children's oral-health risks. 17 UK-based researchers have suggested that, to protect children's oral health, "health visitors" (i.e., publichealth nurses) should receive training in oral-health promotion, including how to perform oral-health risk assessments and guidance on evidence-based, up-to-date prevention measures. 18 On the other hand, in the US the "dental home" has been developed to foster a comprehensive, sustained, coordinated, familycentered approach to providing oral-health care among children.…”
Section: Discussionmentioning
confidence: 99%